Plasma amino acid and performance subsequent to nutritional supplementation during an endurance run - Lennon, S.; Miller, S.; Ebbeling, C.; Maresh, C.; Armstrong, L.; Rodriguez, N. (Medicine & Science in Sports & Exercise, 1998)
This study assessed: a) plasma amino acid responses following carbohydrate supplemented exercise, and b) the relationship between amino acid and performance after supplementation. Male runners (N = 9) performed three trials of a two-hour 65% VO2max treadmill run; one with protein, one with carbohydrate, and one with a placebo ingestion during the effort. Amino acids, branched-chain amino acids, large neutral amino acids, tryptophan, and free fatty acids were measured. Supplement induced changes in amino acids related to central fatigue were observed but those changes did not impact on performance. Implication. Amino acid alterations resulting from CHO supplementation that are related to central fatigue did not affect endurance running performance.